Distribución geoespacial y perfil clínico-epidemiológico de pacientes con lepra atendidos en el Hospital Regional de Loreto, 2015 – 2023 - Moreno Soto, Angel Alfrando (2024)
Objectives: To analyze the geospatial distribution and clinical-epidemiological characteristics of patients with Leprosy treated at the Regional Hospital of Loreto during the period 2015 and 2023. Methods: Cross-sectional observational study using QGIS v3.28.4 software to analyze the geospatial distribution of Leprosy cases in the Regional Hospital of Loreto. Results: The study included 67 patients from the Leprosy program, 49.2% were older adults and 61.2% were men. The majority (74.6%) did not complete basic education. It was observed that 31.3% were new cases, while 34.3% were relapsed patients. More than 44.8% had more than 5 skin lesions, and 37.3% showed some degree of disability. Regarding classification, 59.7% were multibacillary, with a predominance of undifferentiated leprosy (64.1%) and lepromatous leprosy (23.9%). Multibacillary therapy was applied to 53.7%. In terms of geospatial distribution, notable clusters were identified in Pebas, Nauta and particularly in Iquitos, where 83.6% of cases were concentrated, with two clusters in the districts of Iquitos and Belen. The age distribution showed heterogeneity in Iquitos, with a tendency to be over 60 years of age. Multibacillary Leprosy in Iquitos was homogeneous, with 95.7% of cases of relapse admission. Conclusions: A notable conglomeration of cases was observed in the city of Iquitos according to geospatial distribution. The predominant classification was multibacillary, highlighting the high proportion of relapse cases in the same city.